S-Nitrosylation of Histone Deacetylase 2 by Neuronal Nitric Oxide Synthase as a Mechanism of Diastolic Dysfunction. Issue 19 (11th May 2021) - Yoon, Somy; Kim, Mira; Lee, Hangyeol; Kang, Gaeun; Bedi, Kenneth; Margulies, Kenneth B.; Jain, Rajan; Nam, Kwang-Il; Kook, Hyun; Eom, Gwang Hyeon
Abstract : Background: Although the clinical importance of heart failure with preserved ejection fraction has been extensively explored, most therapeutic regimens, including nitric oxide (NO) donors, lack therapeutic benefit. Although the clinical characteristics of heart failure with preserved ejection fraction are somewhat heterogeneous, diastolic dysfunction (DD) is one of the most important features. Here we report that neuronal NO synthase (nNOS) induces DD by S-nitrosylation of HDAC2 (histone deacetylase 2). Methods: Two animal models of DD—SAUNA (SAlty drinking water/Unilateral Nephrectomy/Aldosterone) and mild transverse aortic constriction mice—as well as human heart samples from patients with left ventricular hypertrophy were used. Genetically modified mice that were either nNOS-ablated or HDAC2 S-nitrosylation–resistant were also challenged. N(ω)-propyl-L-arginine, an nNOS selective inhibitor, and dimethyl fumarate, an NRF2 (nuclear factor erythroid 2–related factor 2) inducer, were used. Molecular events were further checked in human left ventricle specimens. Results: SAUNA or mild transverse aortic constriction stress impaired diastolic function and exercise tolerance without overt systolic failure. Among the posttranslational modifications tested, S-nitrosylation was most dramatically increased in both models. Utilizing heart samples from both mice and humans, we observed increases in nNOS expression and NO production. N(ω)-propyl-L-arginine alleviated the development of DD in vivo. Similarly, nNOS knockout mice were resistant to SAUNA stress. nNOS-induced S-nitrosylation of HDAC2 was relayed by transnitrosylation of GAPDH. HDAC2 S-nitrosylation was confirmed in both DD mouse and human left ventricular hypertrophy. S-nitrosylation of HDAC2 took place at C262 and C274. When DD was induced, HDAC2 S-nitrosylation was detected in wild-type mouse, but not in HDAC2 knock-in mouse heart that expressed HDAC2 C262A/C274A. In addition, HDAC2 C262A/C274A mice maintained normal diastolic function under DD stimuli. Gene delivery with adenovirus-associated virus 9 (AAV9)–NRF2, a putative denitrosylase of HDAC2, or pharmacological intervention by dimethyl fumarate successfully induced HDAC2 denitrosylation and mitigated DD in vivo. Conclusions: Our observations are the first to demonstrate a new mechanism underlying DD pathophysiology. Our results provide theoretical and experimental evidence to explain the ineffectiveness of conventional NO enhancement trials for improving DD with heart failure symptoms. More important, our results suggest that reduction of NO or denitrosylation of HDAC2 may provide a new therapeutic platform for the treatment of refractory heart failure with preserved ejection fraction. Abstract : Supplemental Digital Content is available in the text.